Superhard CrN/MoN films with multilayer architecture - Pogrebnjak, A. D. (2018)
Main regularities of the formation of microstructure and properties ofmultilayer nanostructured CrN/MoN films with periodically changing architecture of layers were considered. Coatings were fabricated by vacuum-arc evaporation of the cathodes (Arc-PVD) in nitrogen atmosphere (pN was 0.4, 0.09 and 0.03 Pa). CrN and γ-Mo2N nitride phases with fcc lattices and a small volume of metastable MoNx cubic phase were formed in the films at pN = 0.4 Pa. The decrease of pN to 0.09 Pa causes the formation of β-Cr2N hexagonal phase. Preferential crystallographic orientation changes from [311] to [111] and [200] when bias voltage Ub is −20, −150 and −300 V respectively. The nanocrystallites size in coatings with bilayer thickness λ = 44 nm decreases to 5.8 nm. The microdeformation grows from 0.4 to 2.3% when Ub changes to −20 V. Coatings show high hardness of 38–42 GPa and H/E = 0.107. In a couple with results of tribological tests, coatings demonstrate strong wear resistance, which makes them appropriate and promising for industrial applications as protective ones. The effect of deposition conditions (pN, Ub, λ) on composition, structure, hardness, toughness and wear resistance was studied to achieve superior mechanical and physical properties of coatings with long lifetime in harsh environment.